Book Review: What time is the 9:20 bus? A Journey to a Meaningful Life, Disability and All, by Lucinda Hage (2014) - Garcia, Aedan (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2019)
This book review considers the challenges of raising a child with a developmental disability as seen in the book What time is the 9:20 bus? by Lucinda Hage. Beyond being an emotional and compelling narrative of a mother struggling to navigate Canada’s medical and social support systems, the book is also an excellent introduction to the fields of bioethics, disability ethics, and resource allocation ethics.